Pengembangan Sistem Informasi Manajemen Reservasi SAFA Guesthouse Malang - Dwi Susanti; Nurudin Santoso; Lutfi Fanani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
SAFA Guesthouse is a private enterprise working on a reservation room, every customer making a reservation has to cross an on-line service provider called airy. Every customer's list of room reservations goes to an airy database, so SAFA Guesthouse cannot access the original data of the reservation room transaction. In the system provided by airy there's only management of the reservation data, and there's even a lot of activities that can't be regulated in the airy system which is employee data management, logbook management, employee schedule management, management of the reservation process (check-in and check-out) and management of room hygiene status. According to the problem, the solutions came with the website technology of the management of the SAFA guesthouse reservation implemented in the framework Laravel. Requirement Engineering were the first step in developing a system in this research to result in 45 functional requirements and 1 non-functional requirement. In requirement engineering, there are also 2 actors who will use the system if they have passed the development stage, namely Customer and Front office. After the requirement engineering are carried out the design phase that produces sequence diagrams, class diagrams, component design, database design and interface design, then the implementation phase is carried out. The development method used in this study is the rapid application development method and using HTML, CSS, Javascript and PHP programming languages. Testing in this research uses the white box method that produces 100% valid grades, the white box test with 100% valid results and RAD test results that produce 100% valid result.